Nationalism and Federalism in Yugoslavia, 1962-1991 - Ramet, Sabrina P. (Indiana University Press, 1992)
This book seeks to demonstrate that, with the multifaceted reform set in motion between 1963 and 1965, the Yugoslav political system acquired, domestically, the basic features of an international balance-of-power system. These features account for the basic pattern and dynamics of Yugoslav politics to the present day.